DATA EVERYWHERE: HIDING INFORMATION IN FACEBOOK GROUPS - Bechmann, Anja (AoIR Selected Papers of Internet Research, 2014)
User data mining is a necessary and desirable commodity to most internet companies and in highly interoperable services where data flows across companies and platforms there seem to be no boundaries for data mining. The largest, most interoperable, and diversified social media data company on the internet is Facebook. The company collects personal and sensitive data about the user across devices and services in various contexts ranging from activity on Facebook to behavior on external websites, pictures from Instagram, playlists from Spotify, and running routes in Runkeeper. The users share these data paths of their lives with their network of friends, Facebook, external companies, advertising agencies and app developers. Bechmann (2015) shows that young Danes use especially Facebook groups as their primary privacy filter to avoid information being shared across services and with all their Facebook friends. The aim of this paper is to analyze what kind of data is shared on Facebook with a focus on open, closed and secret Facebook groups. Methodologically, the paper primarily draws on API Facebook wall and group data retrieval and interviews with 8 Danish high school students and 1 American college student between 18-20 years old. The study will draw perspectives to preliminary results from a broad Facebook API study of 1000 Danes (sample mirroring the Danish population demographics) in the conference presentation. The analysis will make use of content analysis as a combination of manual coding and software supported counting and classification of words according to topics.